Role of personality traits and working memory capacity in scalar implicature computation among L2 Malay adults - Khorsheed, Ahmed (2021)
When we say that Some people have lungs, we implicate that not all people have lungs. This scalar implicature arises when we produce a weaker expression instead of a stronger one. Studies on bilingual adults suggest that L2 learners, regardless of their proficiency level, are sensitive to pragmatic violations and they exhibit a superior pragmatic ability on a par with monolingual control groups. However, the evidence obtained from these studies is largely one-dimensional stemming from offline tasks that provide limited information about implicature processing. The reason why some individuals tend to vary considerably in the consistency with which they interpret under-informative sentences also remains under-explored in L2 context. The present study addressed this issue by investigating scalar implicature computation among L2 adults using an online sentence verification paradigm similar to that of Bott and Noveck whereby participants are required to judge the veracity of categorical under-informative sentences. The study also examined how individual differences in personality traits, working memory capacity, and L2 proficiency would modulate participants’ pragmatic responses and processing times. L2 Malay undergraduate students at two proficiency levels, modest and competent, were recruited to participate in two experiments on scalar implicatures. While the first experiment focused on the role of personality traits in scalar implicature computation, the second focused on the role of the working memory capacity in the same inferential process. The results revealed that those with weaker English proficiency tended to be significantly less sensitive to scalar implicatures than those with proficiency advantage. The two proficiency groups also took significantly longer processing times to compute the pragmatic interpretation than the logical interpretation. The pragmatic processing slowdown was also significantly larger in the modest English group than that in the competent English group, and thus evidence denoting that scalar implicature computation is cognitively demanding among those with weaker English proficiency. The results further revealed that the pragmatic responses and their processing slowdowns were influenced by various personality and autistic traits. Those who recorded a high score on the Autism Spectrum Quotient tended to be more literal in their pragmatic readings and they were significantly slower in their reaction times compared to those with low autistic scores. All the participants who scored high on trait Neuroticism also tended to be significantly slower in processing the pragmatic interpretations compared to their peers with low neuroticism. However, the results did not show any significant relationship between participants’ working memory capacity and the proportion of their pragmatic interpretations and their processing times. This study makes a significant new intellectual contribution to second language research by testing scalar implicatures using an online testing paradigm. The study also provides breakthrough empirical evidence which indicates that the pragmatic ability among L2 adults increases with the increase of L2 proficiency, and thus a novel finding which opposes all previous assumptions obtained from studies employing offline tasks in the literature. These findings provide empirical insights into how L2 learners process scalar implicatures and therefore useful implications for the processing theories in experimental pragmatics and second language acquisition.